Management of palm oil mill effluent through production of cellulases by filamentous fungi - Rashid, Shah Samiur; Alam, Md. Zahangir; Abdulkarim, Mohd Ismail; Mohd. Salleh, Hamzah (Springer, 2009)
A laboratory scale study to evaluate the potentiality of filamentous fungi for the production of cellulolytic enzymes using palm oil mill effluent (POME)as a basal medium was initiated. A total of 25 filamentous fungi in which 16 filamentous fungi were isolated and purified from oil palm industrial residues and 9 strains from laboratory stock were screened using POME with 1% total suspended solids. Trichoderma reesei RUT C-30 was identified as a potential strain for cellulolytic enzyme production as compared to other genera of Aspergillus, Penicillum, Rhizopus, Phanerochaete, Trichoderma and basidiomycete groups. The results showed that T. reesei RUT C-30 gave the highest filter paper cellulase and carboxy methyl cellulase activity of 0.917 and 2.51 U/ml respectively at day 5 of fermentation. Other parameters such as growth formation, pH, filterability and total biosolids were observed to evaluate the bioconversion process.